2022
DOI: 10.1021/acssuschemeng.2c03693
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Ni/ZSM-5@MCM-41 Catalyst for CO2 Methanation

Abstract: In this work, a Ni-based catalyst supported on a core–shell structure catalytic carrier material (Ni/ZSM-5@MCM-41) based on kaolinite tailings is reported, which exhibits excellent CO2 methanation performance at atmospheric pressure. At 400 °C, CO2 conversion and CH4 selectivity reach 80 and 97% with the space velocity of 12,000 mL gcat –1 h–1, respectively, and it can maintain good stability during the 80 h stability test. Compared with traditional Ni/ZSM-5 and Ni/MCM-41 catalysts, Ni/ZSM-5@MCM-41 has more su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The low-angle XRD pattern of MCM-41 revealed diffraction peaks corresponding to the (100), (110), and (200) planes, which were in accordance with a highly ordered hexagonal mesoporous structure. 42 As can be seen, only the most intense characteristic peak of MCM-41 was observed for MCM-41/NH-SO 3 H due to the reduction of the scattering contrast between the channel walls of MCM-41 and immobilized components. However, the feature of MCM-41 was preserved in the solid acid−base bifunctional catalyst.…”
Section: Resultsmentioning
confidence: 90%
“…The low-angle XRD pattern of MCM-41 revealed diffraction peaks corresponding to the (100), (110), and (200) planes, which were in accordance with a highly ordered hexagonal mesoporous structure. 42 As can be seen, only the most intense characteristic peak of MCM-41 was observed for MCM-41/NH-SO 3 H due to the reduction of the scattering contrast between the channel walls of MCM-41 and immobilized components. However, the feature of MCM-41 was preserved in the solid acid−base bifunctional catalyst.…”
Section: Resultsmentioning
confidence: 90%
“…1(a), and it can be seen that there are obvious characteristic diffraction peaks at 2 θ = 7.8°, 8.7°, 23.1°, 23.8° and 24.3°, correspond to (011), (200), (051), (511) and (313) diffraction peaks, respectively. 16–19 This indicates that the insertion of Ga atoms did not change the structure of the zeolite. In addition, any characteristic diffraction peaks for Ga-compounds were not found.…”
Section: Resultsmentioning
confidence: 93%
“…[ 1 ] DRM has been regarded as a promising route to tackle excess greenhouse gas emissions as it converts the two greenhouse gases of CO 2 and CH 4 to syngas (H 2 and CO), a key chemical feedstock for large‐scale industrial processes to produce fuels, high‐value‐added chemicals, and clean hydrogen energy. [ 2–26 ] However, there are two major obstacles to this scenario. One is high energy consumption for DRM as it is a highly endothermic reaction (Δ H 298 = 247 kJ mol −1 ), requiring a high reaction temperature (usually above 700 °C).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–6,27–46 ] Intensive studies have identified metallic Ni‐based catalysts as the most promising candidate for both conventional thermocatalytic and light‐driven catalytic DRM owing to their earth‐abundance, inexpensiveness, and high initial activity comparable to precious metal catalysts. [ 9–14,18–34 ] However, they are vulnerable to deactivation due to severe coking, blocking their widely practical application. As the side reactions of coking are thermodynamically unavoidable, [ 12,13 ] the key issue of the catalyst deactivation could only be tackled through rationally designing unique Ni‐based catalysts that could kinetically inhibit coking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation